2011
DOI: 10.1158/0008-5472.can-10-4366
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitating Cancer Immunosurveillance: Selective Stimulation of DLL1-Notch Signaling in T cells Rescues T-cell Function and Inhibits Tumor Growth

Abstract: Deficiencies in immune function that accumulate during cancer immunoediting lead to a progressive escape from host immune surveillance. Therapies that correct or overcome these defects could have a powerful impact on cancer management, but current knowledge of the types and mechanisms of immune escape are still incomplete. Here we report a novel mechanism of escape from T cell immunity that is caused by reduction in levels of the Delta family Notch ligands DLL1 and DLL4 in hematopoietic microenvironments. An i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
81
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 48 publications
3
81
0
Order By: Relevance
“…Other recent studies have shown that Notch signaling can be activated by soluble forms of the ligands Jagged and Delta (19)(20)(21). The soluble Jagged and Delta have different effects on tumor progression--soluble Delta inhibits tumor growth (22,23), whereas soluble Jagged strongly aggravates the malignant progression of cancer. More specifically, Jagged plays an important role in inducing epithelial to mesenchymal transition (EMT) as well as promoting cells to acquire cancer stem cell (CSC) properties (20).…”
mentioning
confidence: 99%
“…Other recent studies have shown that Notch signaling can be activated by soluble forms of the ligands Jagged and Delta (19)(20)(21). The soluble Jagged and Delta have different effects on tumor progression--soluble Delta inhibits tumor growth (22,23), whereas soluble Jagged strongly aggravates the malignant progression of cancer. More specifically, Jagged plays an important role in inducing epithelial to mesenchymal transition (EMT) as well as promoting cells to acquire cancer stem cell (CSC) properties (20).…”
mentioning
confidence: 99%
“…Aside from the notch-mediated responses highlighted in our Review, notch has also been implicated in: cancer immunosurveillance in both circulating tumour cells 11 and the bone marrow; 12 epigenetics; 13 and proteomic modifications. 14 Thus, the effects of the notch pathway on the development of prostate tumours, their response to treatment and cancer stem cells require extensive examination, which is further warranted by the great promise of combined antiangiogenic and antitumorigenic inhibition of the notch pathway.…”
Section: Laure Marignolmentioning
confidence: 97%
“…Since the Notch system lies at a juncture of an interactive cell signaling network, activation or inhibition of selective Notch markers may serve as unique predictors of immune reconstitution, re-established tumor immunosurveillance and direct anticancer effects following cancer immunotherapy. Our work revealed that tumor and its derivative proangiogenic factors such as the Vascular Endothelial Growth Factor (VEGF) [17,18] down-regulates the expression of Delta-like Notch ligands in the hematopoietic compartment of mice as well as humans, and the resulting decrease in ligand-induced Notch activation leads to defects in T cells [16]. Paradoxically, we also recently discovered that stimulation of DLL1-mediated Notch signaling by over-expression of DLL1 in the hematopoietic compartment or by systemic administration of a prototypic therapeutic reagent, clustered multivalent DLL1, was sufficient to correct tumor-induced defects in T lymphocyte differentiation, and enhance T cell anti-tumor immunity to produce significant tumor inhibition in mouse lung cancer models [16].…”
Section: Introductionmentioning
confidence: 98%
“…Besides the established roles of the Notch system described above, our recent discovery of its significance for antitumor effector functions and memory [16] reveals important gaps in current knowledge. Since the Notch system lies at a juncture of an interactive cell signaling network, activation or inhibition of selective Notch markers may serve as unique predictors of immune reconstitution, re-established tumor immunosurveillance and direct anticancer effects following cancer immunotherapy.…”
Section: Introductionmentioning
confidence: 99%